Pengaruh Pemberian Kompres Hangat Suprapubik Terhadap Pemulihan Reflek Vesica Urinaria Pada Pasien Post Spinal Anestesi Di RSU PKU Muhammadiyah Bantul - Winda Arfian Sari; Rosa Delima Ekwantini; Agus Sarwo Prayogi (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2017)
Spinal anesthesia causes urinary retention because the urethral sphincter muscle doesn't respond to urination desire. Whencircumstances continue the pressure inhibits the flow of urine occurs hydroureter, hydronephrosis and gradually kidneyfailure. Suprapubic warm compresses activated dopaminergic transmission in the mesolimbic central nervous system thateffectively improve circulation speeds recovery of vesica urinary reflex. This research is aimed to know the effect of warmcompress on the vesica urinaria recovery reflex in post spinal anesthesia patient at RS PKU Muhammadiyah Bantul. Thisstudy was an experimental study with quasy experiment type with Non Equivalent Control Group After Only Design. Thetreatment provided was suprapubic warm compress. Consecutive sampling with 40 respondents divided into control andintervention group that undergo spinal anesthesia at RSU PKU Muhammadiyah Bantul. Data analysis was done by Chisquare. In control group, 9 respondents (45%) had vesica urinary reflex recovery ? 8 hours, while in intervention group, 16respondents (20%) had vesica urinary reflex ? 8 hours. Chi Square test resulted on p value 0.022 (?0,05). There is an effect ofsuprapubic warm compress toward vesica urinary reflex recovery in post spinal anesthesia patients at RSU PKUMuhammadiyah Bantul.